Testosterone Level and Coronary Artery Disease in Iranian Men; a Systematic Review - Shojaeefar, Ehsan; Aghaei, Kamyar; Abbasi Fashami, Mahta; Nematollahi, Shahrzad; Aliakbari, Fereshteh; Abedi, Amir Reza (Archives of Men’s Health, 2021)
Coronary artery disease (CAD) is among the most common cardiovascular diseases (CVDs), caused by the formation of plaques of lipids, calcium, and inflammatory cells. In Iran, CAD is responsible for about 50% of all deaths per year. There is also a probability of the role of androgens deficiency in CAD in men. We aimed to systematically review all the related original studies to achieve an overall insight into the associations of testosterone and CAD in Iranian men. MedLine, Web of Science, Scopus, and Google scholar databases were searched from inception to January 2021. All types of studies on Iranian men older than 40 years of age, reporting results of comparing testosterone in normal individuals and those with CAD were included. The main findings of the articles were compared to achieve an overall statement. Ultimately, six studies were included. Most (66.7%) had directly stated that lower levels of testosterone are associated with CAD or the level of testosterone is lower in patients with proven CAD. Among them, in 3 (50%) studies, the mean age of the participants had no significant difference between patients with CAD and the normal group. It is clear that low testosterone level is associated with increased risk of cardiovascular events but it is not definitely determined whether it is independent of age in Iranian men. Further well-designed studies are needed to clearly exclude all confounding variables including age and show the net effect of testosterone on CAD.